2016
DOI: 10.15171/jrip.2016.17
|View full text |Cite
|
Sign up to set email alerts
|

Association of metabolic syndrome with serum fibroblast growth factor 21 in kidney transplanted patients

Abstract: Introduction: Fibroblast growth factor 21 (FGF21) is a metabolic regulator with multiple beneficial effects on glucose and lipid homeostasis and insulin sensitivity. Objectives: The aim of this study was to investigate the relation between the serum level of FGF21 with and metabolic syndrome (MS) in kidney transplant recipients. Patients and Methods: We performed a cross-sectional study on 86 stable renal transplant recipients to detect possible relation between serum FGF21 level and MS during October 2014 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…FGF21 is a member of FGF family, which induces beneficial effects in multiple organs in an endocrine manner [22]. Increasing clinical studies have demonstrated that circulating FGF21 levels are dramatically increased in patients with various kidney diseases, including chronic kidney disease (CKD) [23,24], kidney transplantation [25,26], ESRD [27], early-stage diabetic kidney disease [28], acute renal dysfunction [29], and long-term peritoneal dialysis [30], indicating that an increase in FGF21 levels above baseline is a stress response to induce renal protection. This hypothesis was confirmed by a subsequent study, which showed that the administration of FGF21 maintained renal function in mice with CKD [31].…”
Section: Discussionmentioning
confidence: 99%
“…FGF21 is a member of FGF family, which induces beneficial effects in multiple organs in an endocrine manner [22]. Increasing clinical studies have demonstrated that circulating FGF21 levels are dramatically increased in patients with various kidney diseases, including chronic kidney disease (CKD) [23,24], kidney transplantation [25,26], ESRD [27], early-stage diabetic kidney disease [28], acute renal dysfunction [29], and long-term peritoneal dialysis [30], indicating that an increase in FGF21 levels above baseline is a stress response to induce renal protection. This hypothesis was confirmed by a subsequent study, which showed that the administration of FGF21 maintained renal function in mice with CKD [31].…”
Section: Discussionmentioning
confidence: 99%
“…For details, a China cohort revealed that higher FGF21 levels increased renal function decline in patients undergoing coronary angiography [ 32 ]. Additionally, two studies have found that FGF21 was inversely related to renal function in kidney transplant patients [ 37 , 38 ]. As the limited eligible studies, no further meta-analysis was performed for this part.…”
Section: Resultsmentioning
confidence: 99%
“…Since multiple, favorable FGF21 effects on glucose and lipid metabolism and insulin sensitivity have been reported, FGF21 might be a biomarker that influences metabolic syndrome (MetS) and type 2 diabetes (T2DM) pathophysiology. 3 6 It may also be a therapeutic agent for treating diabetes and other obesity-related metabolic disorders.5 FGF21 has also been shown to be a potent metabolic regulator. 5 7 8 9 In addition, research has shown that increased FGF21 levels are associated with MetS in Asian individuals.…”
Section: Introductionmentioning
confidence: 99%